PENGEMBANGAN MULTIMEDIA INTERAKTIF MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN SELF REGULATED LEARNING SISWA SEKOLAH DASAR - Elsa Kurnia Windhyastuti; Rahayu Kariadinata; Ardi Dwi Susandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conventional learning in mathematics subjects has an impact on low problem-solving abilities and self-regulated learning. This study was conducted to develop interactive mathematics multimedia assisted by Articulate Storyline that is feasible, practical, and effective to improve problem-solving abilities and self-regulated learning of fourth-grade elementary school students. This research is a Research and Development developed with the ADDIE design with 5 stages, namely: Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study were fourth-grade elementary school students. Data collection techniques used were expert validation sheets, student response questionnaires, teacher responses, self-regulated learning questionnaires, pretest and posttest results, and learning observations. Data were analyzed descriptively quantitatively and qualitatively. The results showed that interactive multimedia was proven to be feasible to use with an average score percentage of 77.4% for material expert validation and 79% for media expert validation. The results of the practicality of the media obtained an average score of student responses in small groups of 80% with a good category, and 80.2% with a very good category score for the large group student response score, as well as a teacher response questionnaire with an average score percentage of 80% in the good category. The results of the effectiveness of the media are shown by the pretest results of 53 and the posttest results of 85.6 with an N-Gain result of 0.69 in the moderate category. In addition, from the self-regulated learning questionnaire with an average score percentage of 39.4% in the less good category to 79% in the good category. It can be concluded that interactive mathematics multimedia assisted by Articulate Storyline is feasible, practical, and effective to be used as a learning medium in improving problem-solving abilities and self-regulated learning of elementary school students.